The novel Fh8 and H fusion partners for soluble protein expression in Escherichia coli : a comparison with the traditional gene fusion technology - Costa, Sofia Judite (2013)
The Escherichia coli host system is an advantageous choice for simple and inexpensive recombinant protein production but it still presents bottlenecks at expressing soluble proteins from other organisms. Several efforts have been taken to overcome E. coli limitations, including the use of fusion partners that improve protein expression and solubility. New fusion technologies are emerging to complement the traditional solutions. This work evaluates two novel fusion partners, the Fh8 tag (8 kDa) and the H tag (1 kDa), as solubility enhancing tags in E. coli and their comparison to commonly used fusion partners. A broad range comparison was conducted in a small-scale screening and subsequently scaled-up. Six difficult-to-express target proteins (RVS167, SPO14, YPK1, YPK2, Frutalin and CP12) were fused to eight fusion tags (His, Trx, GST, MBP, NusA, SUMO, H and Fh8). The resulting protein expression and solubility levels were evaluated by sodium dodecyl sulfate polyacrylamide gel electrophoresis before and after protein purification and after tag removal. The Fh8 partner improved protein expression and solubility as the well-known Trx, NusA or MBP fusion partners. The H partner did not function as a solubility tag. Cleaved proteins from Fh8 fusions were soluble and obtained in similar or higher amounts than proteins from the cleavage of other partners as Trx, NusA or MBP. The Fh8 fusion tag therefore acts as an effective solubility enhancer, and its low molecular weight potentially gives it an advantage over larger solubility tags by offering a more reliable assessment of the target protein solubility when expressed as a fusion protein.